Bifunctional magnetic ZnCdSe/ZnS quantum dots nanocomposite-based lateral flow immunoassay for ultrasensitive detection of streptomycin and dihydrostreptomycin in milk, muscle, liver, kidney, and honey. (16th April 2023) - Chen, Jiayi; Jiang, Jiali; Liang, Jinxuan; Wu, Han; Chen, Liping; Xu, Zhenlin; Lei, Hongtao; Li, Xiangmei
Highlights: Bifunctional magnetic quantum dots nanocomposite was synthesized. An immunoassay based on magnetic quantum dots was developed for streptomycin detection. The sensitivity of the developed assay was 42-fold higher than the similar methods. A portable reader was self-developed and used for rapid quantification. Abstract: In this study, bifunctional magnetic ZnCdSe/ZnS quantum dots nanocomposite (MQNs) were synthesized, and firstly used to develop a lateral flow immunoassay (LFIA) for streptomycin (STR) and dihydrostreptomycin (DHSTR) detection in milk, muscle, liver, kidney, and honey simultaneously. The fluorescence signal of MQNs was 9-fold stronger than that of the original quantum dots. The detection limits of the established MQNs-LFIA for STR and DHSTR in five samples were 0.08–1.78 μg/kg, the quantitation limits were 0.26–5.87 μg/kg, the recoveries were between 85.0% and 120.0%, and the coefficient of variations were between 0.8% and 19.3%, respectively. The sensitivity was up to 42-fold more sensitive than the reported LFIAs. The single blind test results of 25 samples were consistent with that of the confirmation method (R 2  ≥ 0.99). Besides, a portable reader was self-developed and used for rapid quantification. Our study demonstrated MQNs as a promising signal-amplifying tag can be used for ultrasensitive detection of chemical contaminants in foods.